2013
DOI: 10.1097/sla.0b013e318287ab73
|View full text |Cite
|
Sign up to set email alerts
|

Pathohistological Subtype Predicts Survival in Patients With Intraductal Papillary Mucinous Neoplasm (IPMN) of the Pancreas

Abstract: Evaluation of IPMN subtypes supports postoperative patient prognosis prediction. Therefore, subtype differentiation could lead to improvements in clinical management. Potentially identifying subgroups with the need for adjuvant therapy may be possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
107
1
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 24 publications
4
107
1
11
Order By: Relevance
“…One previous study has reported that gastric-and intestinal-type intraductal papillary mucinous neoplasms demonstrate less malignant potential than pancreatobiliary-type intraductal papillary mucinous neoplasms. 47 Distler et al 48 have reported that pancreatobiliary-type intraductal papillary mucinous neoplasm is strongly associated with advanced tumor stage in comparison with intestinal-type intraductal papillary mucinous neoplasm. Moreover, pancreatobiliary-type intraductal papillary mucinous neoplasm demonstrates higher local recurrence and metastatic rates compared with other histological subtypes of intraductal papillary mucinous neoplasm, including intestinal, gastric, and oncocytic types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous study has reported that gastric-and intestinal-type intraductal papillary mucinous neoplasms demonstrate less malignant potential than pancreatobiliary-type intraductal papillary mucinous neoplasms. 47 Distler et al 48 have reported that pancreatobiliary-type intraductal papillary mucinous neoplasm is strongly associated with advanced tumor stage in comparison with intestinal-type intraductal papillary mucinous neoplasm. Moreover, pancreatobiliary-type intraductal papillary mucinous neoplasm demonstrates higher local recurrence and metastatic rates compared with other histological subtypes of intraductal papillary mucinous neoplasm, including intestinal, gastric, and oncocytic types.…”
Section: Discussionmentioning
confidence: 99%
“…In ampullary carcinoma, the pancreatobiliary type also demonstrates significantly deeper tumor invasion (that is, pT classification) and more frequent lymph nodal, perineural, duodenal, and pancreatic invasion than intestinal ampullary carcinomas. 13,49 In addition, intestinal type tumors demonstrate significantly better patient survival than pancreatobiliary type neoplasms from various gastrointestinal tract tumors, including intraductal papillary mucinous neoplasm 48 and ampullary 49 and gastric 50 carcinomas. In concordance with the results of previous studies on the prognostic implications of the morphologic and immunophenotypic classifications of other gastrointestinal tumors, the intestinal immunophenotype adenocarcinomas we examined in our present study were associated with significantly better patient survival outcomes than small intestinal adenocarcinomas of other immunophenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Furthermore, studies have reported conflicting evidence on whether the histologic IPMN subtype has prognostic significance. [8][9][10][11][12] The Verona consensus meeting in 2013 recently led to the publication of guidelines for pathologic reporting of IPMN with the recommendation that pathologists provide a histologic subtype. 13 Although most previous studies used morphology and immunohistochemistry to designate the IPMN subtype, this is not necessarily implemented as standard practice.…”
mentioning
confidence: 99%
“…Epithelial subtyping helps to explain this well documented survival advantage through the observation that each has a distinct path and rate of progression to a specific form of pancreatic cancer. Subtype analysis of these specific cancers reveals that much of the overall survival advantage is due to the more favorable prognoses of colloid and oncocytic carcinoma compared to tubular adenocarcinoma, which has a similar overall survival to classic PDAC [8,10,11] .…”
Section: Clinicopathological Features Of Ipmnmentioning
confidence: 99%
“…IPMN are classified further into 4 epithelial subtypes based upon mucin expression and morphology: gastric, intestinal, pancreatobiliary and oncocytic [8][9][10] . The gastric subtype is the most common overall and is generally found in the periphery of the pancreas in the form of BD-IPMN.…”
Section: Clinicopathological Features Of Ipmnmentioning
confidence: 99%